Analysis of sudden infant death syndrome coverage in Canadian newspapers. (December 2018) - Ahmed, Sadia; Mitchell, Ian; Wolbring, Gregor
Sudden infant death syndrome (SIDS; also known as crib death) describes the sudden unexpected death of an infant under one year of age, which remains unexplained after a thorough investigation. SIDS is a public health concern. It is the fourth leading cause of infant death in Canada. Newspapers are a major source of health information for the public, shape public perceptions and can direct the discussion around issues. Despite the potential influence of newspapers, no study has examined the portrayal of SIDS in Canadian newspapers over time. The purpose of our study was to gain an understanding of SIDS coverage in Canadian English language newspapers using the Canadian Newsstream database from 1970 to 2015 and the historical database: The Globe and Mail from 1844 to 1977. Generating descriptive quantitative and qualitative data, we noted a decline in SIDS coverage over time. Blame and misdiagnosis were two dominant themes in the coverage of SIDS with many other aspects around SIDS missing; for example, indigenous people, who are at higher risk for SIDS, were rarely mentioned. Our findings suggest problems in the content and frequency of coverage of SIDS that have the potential to shape the public understanding of SIDS.